In Support of Winge's Theory of “Hybridization Followed by Chromosome Doubling” - Tel-Zur, Noemi; Mouyal, Joseph; Zurgil, Udi; Mizrahi, Yosef (Frontiers in Plant Science, 2020)
Polyploidy – or chromosome doubling – plays a significant role in plant speciation and evolution. Much of the existing evidence indicates that fusion of unreduced (or 2n) gametes is the major pathway responsible for polyploid formation. In the early 1900s, a theory was put forward that the mechanism of “hybridization followed by chromosome doubling” would enable the survival and development of the hybrid zygote by providing each chromosome with a homolog with which to pair. However, to date there is only scant empirical evidence supporting this theory. In our previous study, interspecific-interploid crosses between the tetraploid Hylocereus megalanthus, as the female parent, and the diploid H. undatus, as the male parent, yielded only allopentaploids, allohexaploids and 5x-and 6x-aneuploids instead the expected allotriploids. No viable hybrids were obtained from the reciprocal cross. Since H. undatus underwent normal meiosis with regular pairing in the pollen mother cells and only reduced pollen grains were observed, the allohexaploids obtained supported the concept of “chromosome doubling.” In this work we reported ploidy level, fruit morphology and pollen viability and diameter in a group of putative hybrids obtained from an embryo rescue procedure following controlled H. megalanthus × H. undatus crosses, aiming to elucidate, for the first time, the timing and developmental stage of the chromosome doubling. As in our previous report, no triploids were obtained, but tetraploids, pentaploids, hexaploids and 5x-and 6x-aneuploids were found in the regenerated plants. The tetraploids exhibited the morphological features of the maternal parent and could not be considered true hybrids. Based on our previous studies, we can assume that the pentaploids were a result of a fertilization event between one unreduced (2n) female gamete from the tetraploid H. megalanthus and a normal (n) haploid male gamete from H. undatus. All the allohexaploids obtained from the embryo rescue technique where those that regenerated from fertilized ovules 10 days after pollination (at the pro-embryo stage), showing that the chromosome doubling event occurred at a very early development stage, i.e., at the zygote stage or shortly after zygote formation. These allohexaploids thus constitute empirical evidence of “hybridization followed by chromosome doubling.”